Identification of Cellular MicroRNA Coupling Strand Displacement Polymerization and Nicking‐Endonuclease‐Based Cleavage. Issue 12 (16th October 2015) - Miao, Peng; Tang, Yuguo; Zhang, Qi; Bo, Bing; Wang, Jue
Abstract: Invited for this month's cover are collaborators from a group at Suzhou Institute of Biomedical Engineering and Technology, Chinese Academy of Sciences and a group at Shanghai Tenth People's Hospital, Tongji University School of Medicine. The cover picture shows the design of an electrochemical method for cellular microRNA detection coupling strand displacement polymerization and nicking‐endonuclease‐mediated cleavage. Read the full text of the article at 10.1002/cplu.201500249 . Abstract : " … We have focused on the development of a series of biosensors for the detection of microRNAs, one kind of endogenous, small noncoding RNAs that are regarded as potential noninvasive biomarkers and therapeutic targets for corresponding diseases …" Read more about the story behind the cover in the Cover Profile and about the research itself on page 1699 (DOI:10.1002/cplu.201500249 ).